2019
DOI: 10.1016/j.cgh.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Colorectal Cancer in Patients With Acute Diverticulitis: A Systematic Review and Meta-analysis of Observational Studies

Abstract: In a meta-analysis of observational studies of patients with acute diverticulitis, we found the pooled prevalence of colorectal cancer to be 1.9%. The risk of colorectal cancer was significantly higher in patients with complicated diverticulitis than in patients with uncomplicated diverticulitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 52 publications
7
56
1
5
Order By: Relevance
“…A recent systematic review reported a pooled prevalence of colorectal cancer in patients with uncomplicated diverticulitis of 1·3 per cent, compared with 7·9 per cent in patients with complicated diverticulitis. The present study pool had low rates of colorectal cancer, of 0·4 and 2·1 per cent in the no‐antibiotic and antibiotic group respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review reported a pooled prevalence of colorectal cancer in patients with uncomplicated diverticulitis of 1·3 per cent, compared with 7·9 per cent in patients with complicated diverticulitis. The present study pool had low rates of colorectal cancer, of 0·4 and 2·1 per cent in the no‐antibiotic and antibiotic group respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis performed this year, we found a pooled prevalence of colorectal cancer of 1.3% (95% CI 0.1-2.0%) among 3,834 patients (15 studies) with uncomplicated episodes [3]. Further, a recent publication, not included in these meta-analyses, indicated the prevalence of colorectal cancer to be 1.8% in a cohort of 227 patients with uncomplicated diverticulitis [4].…”
Section: Dear Editormentioning
confidence: 99%
“…0·2 to 1·2) per cent prevalence in patients with CT‐proven, left‐sided and uncomplicated (Hinchey 1a) diverticulitis who underwent colonoscopy. The meta‐analysis of Meyer et al . yields a pooled prevalence of 1·3 (95 per cent c.i.…”
mentioning
confidence: 99%